MODEL PEMBELAJARAN DISCOVERY LEARNING SEBAGAI METODE UNTUK MENINGKATKAN PRESTASI BELAJAR - Syari, Siti Ratna; Nuryanti, Lena (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2016)
The base student achievement was the background of this study. The ignoble scores on student achievement, especially in entrepreneurship subject was influenced by the external and internal factors. Learning model could have developed by teachers in the school environment that certainly have a profound influence on learning achievement. SMK Negeri 1 Bandung teachers apply the discovery learning model in entrepreneurship subjects to improve learning achievement of learners. The purpose of this study is to describe: 1) the application of the discovery learning model in class XI SMK Negeri 1 Bandung, 2) learning achievement in class XI AP and UPW SMK Negeri 1 Bandung, 3) The amount of influence discoveries learning model on achievement learning in class XI AP and UPW of SMK Negeri 1 Bandung. Discovery learning model as the independent variable (X), and the dependent variable is learning achievement (Y) with descriptive and verification analysis. The method used in this research was explanatory survey method with simple random sampling technique with 124 respondents used linear regression technique. The findings in this study are as follows: 1) the application of learning model discovery learning in class XI AP and UPW in either category, 2) learning achievement in AP classes and UPW in the high category, 3) learning achievement positively influenced by discovery learning model with a coefficient of determination 21.3%. The Result based on the research, discovery learning model with indicators and different objects recommended as a basis for other studies.Â Keywords: discovery learning model, academic achievement